Low-temperature growth and physical investigations of undoped and (In, Co) doped ZnO thin films sprayed on PEI flexible substrate. (August 2015) - Ben Ameur, S.; Barhoumi, A.; Mimouni, R.; Amlouk, M.; Guermazi, H.
Highlights: A successful deposition of ZnO thin films at low-temperature on PEI substrates was obtained by using the spray pyrolysis. The crystallite size was found to be around 83 nm for ZnO and CZO and 41 nm for IZO. Photoluminescence reveals that all ZnO films have UV emission and visible defects. Wattability properties show that doping by cobalt enhanced the surface roughness. Abstract: ZnO thin films were deposited on polymer substrate Polyethyerimide (PEI) at 250 °C by spray pyrolysis technique. The effects of different doping elements (Co and In) on physical properties of ZnO thin films were investigated. Thin film characterizations were carried out using X-ray diffraction technique, UV–Vis–NIR spectroscopy, Photoluminescence (PL) spectroscopy and the contact angle measurement method. XRD measurement showed a successful growth of crystalline films on polymer substrate at low temperature by the spray pyrolysis process. XRD patterns revealed that all films consist of single ZnO phase and were well crystallized with preferential orientation towards (1 0 1) direction. Doping by cobalt has effective role in the enhancement of the crystalline quality, increases in the band gap according to Burstein Moss effect. Doping with indium leads rather to the decrease of both crystallinity and optical band gap energy value. Photoluminescence of the films showed UV emission (NBE) and visible emission related to defects. The contact angles were measured to study the effect of various doping elements on the hydrophobicity of the film depending on surface roughness. Results showed strong dependence on the doping element. In fact, doping with cobalt element increases the roughness of ZnO films and reinforces the surface from hydrophilic to hydrophobic ( θ  > 90°).